SINTESIS DAN UJI AKTIVITAS ANTIBAKTERI SENYAWA ANALOG PIRAZOLIN TURUNAN 3’BROMOKALKON INTI NAFTALEN - Sriatun Sadiah; Yuharmen '; Jasril ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Analog compound of 3'bromochalcone pyrazoline derivative 5- (3-bromofenil) -3-(naphthalene-2-yl) -1-fenill-4.5-dihydro-1H pirazol (PP2) was synthesized through nucleophilic addition reactions using glacial acetic acid catalyst under microwave radiation. PP2 compound was obtained as yellow crystal with yield of 77.73%. The purity of pyrazoline analog coumpound has been tested using TLC observation, determination of melting point, HPLC analysis and characterized by UV spectroscopy, IR spectroscopy, Mass spectroscopy and NMR spectroscopy. Antibacterial test conducted by the agar diffusion method with concentration of 10 μg/disk dan 30 μg/disk against Gram-positive bacteria, B. subtilis and S. aureus, and Gram-negative bacteria, E. coli and S. typhi. PP2 compound showed that there was a low antibacterial activity. However, the inhibition of PP2 against Gram-positive bacteria is greater than that of Gram-negative bacteria.